2021
DOI: 10.3390/cancers13071582
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Associated Invariant T Cells in Cancer-Friend or Foe?

Abstract: Mucosal associated invariant T (MAIT) cells are a population of unconventional T cells which can bridge the innate and adaptive immune systems. Well-described roles for MAIT cells include host protection against invading bacteria, fungi and viruses. Upon activation, MAIT cells become prolific effector cells, capable of producing a range of cytokines and lytic molecules. In addition to their anti-microbial role, MAIT cells have been implicated in immune responses to cancer, with opposing beneficial and pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…Limiting glycolysis by acutely reducing glucose availability or substituting glucose with galactose also significantly impeded MAIT cell proliferation, providing evidence for glucose availability being a rate limiting step. MAIT cell cytokine production has been reported as defective in numerous human diseases, including cancer, obesity and more recently COVID-19 31,39,40 . Here we show for the first time that MAIT cell proliferation is defect in people with obesity, which may link with the reports of defective host protection in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Limiting glycolysis by acutely reducing glucose availability or substituting glucose with galactose also significantly impeded MAIT cell proliferation, providing evidence for glucose availability being a rate limiting step. MAIT cell cytokine production has been reported as defective in numerous human diseases, including cancer, obesity and more recently COVID-19 31,39,40 . Here we show for the first time that MAIT cell proliferation is defect in people with obesity, which may link with the reports of defective host protection in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…MAIT cells have been detected in a variety of human tumor types, such as colorectal ( 70 , 71 ), cervical ( 72 ), lung ( 73 , 74 ), liver ( 75 ), and kidney cancers ( 76 ). Cancer has an effect on MAIT cell frequency, phenotype, and function, whereas the effect of MAIT cells on cancer may vary greatly from cancer to cancer ( 77 ). Collectively, no conclusion has been drawn on whether MAIT cells play an anti-tumor or a tumor-promoting role in different tumors or microenvironments.…”
Section: Mait Cells and Hematological Malignanciesmentioning
confidence: 99%
“…The MAIT1 subset in newly diagnosed or untreated MM patients was dysfunctional, with reduced IFN-γ (and TNF-α) production, but the ability to produce IFN-γ appeared to be restored in samples from relapsed/refractory MM patients ( 86 , 92 , 99 ). The exact role MAIT cells play in MM remains unclear, but the authors did demonstrate that MAIT cells were capable of killing myeloma cell lines, suggesting the potential for harnessing MAIT cells as an immunotherapy ( 77 , 86 ). A recent prospective study including 216 cases of acute myeloid leukemia (AML) showed that the number of MAIT cells in PB from newly diagnosed AML was significantly reduced, and the degree of reduction was associated with a high-risk cytogenetic karyotype and IDH1/2 mutation, suggesting that the loss of MAIT cell number or function may be associated with AML disease progression ( 103 ).…”
Section: Mait Cells and Hematological Malignanciesmentioning
confidence: 99%
“…As the name suggests, MAIT cells are located in the mucosae, however, they can be found in blood and secondary lymphoid organs [ 1 , 54 ]. As is the case with their other unconventional partners, MAIT cells have recently been shown to have a strong association with anti-tumor responses, and in this regard, we would like to refer you to two excellent reviews by O’Neill et al and Cogswell et al in this issue [ 55 , 56 ].…”
Section: The Three “Unconventionals”: γδ T Nkt and Mait Cellsmentioning
confidence: 99%